2004
DOI: 10.1007/s10439-004-7824-3
|View full text |Cite
|
Sign up to set email alerts
|

The Local Matrix Distribution and the Functional Development of Tissue Engineered Cartilage, a Finite Element Study

Abstract: Abstract-Assessment of the functionality of tissue engineered cartilage constructs is hampered by the lack of correlation between global measurements of extra cellular matrix constituents and the global mechanical properties. Based on patterns of matrix deposition around individual cells, it has been hypothesized previously, that mechanical functionality arises when contact occurs between zones of matrix associated with individual cells. The objective of this study is to determine whether the local distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 59 publications
(94 reference statements)
3
37
0
Order By: Relevance
“…Despite equivalence of the bulk biochemical content, DL could lead to different distributions of the ECM proteins and hence affect mechanical properties [47]. However, finite-element studies [50] on the local distribution of ECM in tissueengineered cartilage concluded that the global aggregate modulus and permeability were largely insensitive to the microscopic matrix distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Despite equivalence of the bulk biochemical content, DL could lead to different distributions of the ECM proteins and hence affect mechanical properties [47]. However, finite-element studies [50] on the local distribution of ECM in tissueengineered cartilage concluded that the global aggregate modulus and permeability were largely insensitive to the microscopic matrix distribution.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study, isotropic linear elastic behavior was reported and 10% strain used to calculate the elastic modulus of scaffolds fabricated as cardiac-mimetic structures; furthermore, 10 to 25% strain was reported as the cardiac-relevant strain range in physiological conditions (Neal et al, 2012). Finally, a finite element study assigned linear elastic elements to a model to predict the mechanical properties of tissue-engineered cartilage constructs (Sengers et al, 2004). Hence, the direct determination of elastic modulus from the linear section of stressstrain curve is appropriate if the possible applications are taken into account.…”
Section: Effect Of Crosslinker Volumementioning
confidence: 99%
“…Rejniak and Anderson derived a plausible set of rules and conditions, including oriented cell division, differentiation, polarization and apoptosis, by which single cells can develop into well-organized acinar structures. Aiming to get a better control over the mechanical properties of tissue-engineered cartilage, Sengers and coworkers [46,47] computationally assessed extracellular matrix (ECM) deposition by chondrocytes ( Figure 1B,E). In a continuous interaction between cell culture and agent-based computational modeling work, the Epitheliome project (see e.g.…”
Section: Introductionmentioning
confidence: 99%